Antihyperlipidemic and Antiinflammatory Activity of Crude Oil Anguilla Marmorata [Q.] Gaimard in White Rats (Rattus Norvegicus) - Jamaluddin Jamaluddin; Khildah Khaerati; Ihwan Ihwan; Yusriadi Yusriadi; Andi Ratihsekarningrum Siradje; Apriyana Soputra; Novita Christiana Ponganan; Klerensia Defneir Titing; Novianti Batti; Andi Mustika; Andi Alfianto; Moh. Rifki; Janes Krisly; Finta Amalinda (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Fish oil has omega-3 and omega-6 fatty acids, which provide health benefits such as prevention of an increase in total cholesterol, triglycerides, and a decrease in blood HDL, as well as being anti-inflammatory agents in humans. The present study was conducted to determine the antihyperlipidemic and anti-inflammatory activities of eel fish (Anguilla marmorata [Q.] Gaimard) oil extracts on white rats (Rattus norvegicus). To test hyperlipidemia, 25 rats were divided into 5 groups and treated with; 1.5 % PEG 400 (negative control), 20 mg simvastatin (positive control), test doses of 18, 36, and 72 mg/kg. The treatments were carried out for 39 days. In investigating the anti-inflammatory activity, 25 white rats were divided into 5 groups; negative control, positive control, three-dose treatments of 22, 44, and 88 mg/200 g. Blood cholesterol levels were measured and percent inflammation was determined. The results showed that the eel oil extracts led to a decreased of total cholesterol levels 49.60 %, triglycerides 31.15 %, and HDL 14.3 %. The percentage of inflammation values ranged from 31.73 to 54.48 %. The findings indicated that the most effective doses for the antihyperlipidemic effect were 72 mg/ kg, while 22 mg/200 g for the anti-inflammatory activity.